Lessons learned from a strangles outbreak on a large Standardbred farm. (29th October 2015) - Christmann, U.; Pink, C.
Summary: Streptococcus equi subspecies (ssp.) equi infection (strangles) remains one of the most frequently diagnosed and costly infectious diseases of horses. Large breeding herds, where a disease outbreak competes for personnel and financial resources needed for foaling management, present a special challenge for equine practitioners. A 15‐month outbreak involving 62 clinical cases of strangles occurred on a large Standardbred breeding farm (average population of 1400 horses). Sixteen asymptomatic horses were found to be PCR (polymerase chain reaction)‐positive for S. equi ssp. equi . During the outbreak, serological samples from 48 clinically normal horses were found to be seropositive for S. equi ssp. equi, confirming herd‐wide exposure. After several clinical cases of strangles had been diagnosed, an intranasal S. equi ssp. equi vaccine was administered to clinically normal horses (n = 558) considered to be at risk of exposure. Strangles complications included 7 fatalities (none in vaccinated horses) and 6 cases of purpura haemorrhagica (4 in vaccinated horses). Midway through the outbreak, injectable, sustained release ceftiofur crystalline free acid (CCFA), given as an initial dose followed by a second dose 4 days later, was used exclusively for systemic antimicrobial treatment of clinically affected and PCR‐positive horses. This antimicrobial regimen coincided with a reduction in disease incidence and eventual resolution of the outbreak. Two horses with persistent guttural pouch infection were endoscopically confirmed as carrier horses. The herd history demonstrated that a strangles outbreak will often result in asymptomatic carrier horses and that identification and treatment of these horses are necessary to eliminate long‐term sources of infection. Ceftiofur crystalline free acid was found to be a suitable antimicrobial due to its activity against S. equi ssp. equi and the efficiencies associated with twice parenteral dosing during a 10‐day treatment period. Occurrence of purpura in 4 vaccinated horses suggests that vaccination should be reserved for healthy seronegative horses and avoided during an active outbreak.